2010
DOI: 10.1021/nl1002608
|View full text |Cite
|
Sign up to set email alerts
|

Graphene and Nanowire Transistors for Cellular Interfaces and Electrical Recording

Abstract: Nanowire field-effect transistors (NW-FETs) have been shown to be powerful building blocks for nanoscale bioelectronic interfaces with cells and tissue due to their excellent sensitivity and their capability to form strongly coupled interfaces with cell membranes. Graphene has also been shown to be an attractive building block for nanoscale electronic devices, although little is known about its interfaces with cells and tissue. Here we report the first studies of graphene field effect transistors (Gra-FETs) as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
343
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 369 publications
(355 citation statements)
references
References 35 publications
4
343
1
1
Order By: Relevance
“…7c). [176] Narrow GFETs (~2 um×3 um) exhibit similar peak-to-peak widths as the nanowireFET (~100 times smaller per area). But GFET devices with large size (~20 um×10 um) detect an average of the extracellular potential from beating cells and yield a broadened peak-to-peak signal width.…”
Section: Gfet Biological Cellular Sensorsmentioning
confidence: 90%
See 1 more Smart Citation
“…7c). [176] Narrow GFETs (~2 um×3 um) exhibit similar peak-to-peak widths as the nanowireFET (~100 times smaller per area). But GFET devices with large size (~20 um×10 um) detect an average of the extracellular potential from beating cells and yield a broadened peak-to-peak signal width.…”
Section: Gfet Biological Cellular Sensorsmentioning
confidence: 90%
“…Even at its early stage of development, such SNR performance equals (or even surpasses) that of well-established techniques like the microelectrode arrays (MEAs) and the planarFET [211] and nanowireFET [176] .…”
Section: Gfet Biological Cellular Sensorsmentioning
confidence: 99%
“…[181][182][183][184][185][186][187][188][189][190][191][192][193][194][195][196][197] The principle of biological detection based on nanowire FETs is very simple. For example, when a single virus particle binds to an antibody receptor linked to the surface of a nanowire FET detector, it yields a conductance change due to the change in nanowire surface charge; when the virus particle subsequently unbinds, the conductance returns to the baseline.…”
Section: Nanobioelectronic Interfacesmentioning
confidence: 99%
“…Only very recently has the operation of graphene in aqueous electrolytes (Figure 6b) for use in biosensors and bioelectronics been reported by several groups. [77][78][79][80][81][82][83][84][85][86] For example, Ang et al 77 first demonstrated the use of solution-gated epitaxial graphene as a pH sensor. Ohno et al 78 reported on electrolyte-gated graphene field-effect transistors for detecting pH and protein adsorption.…”
Section: Grapheneàdetection In Liquid Environmentmentioning
confidence: 99%
“…To further investigate the biocompatibility of graphene with live cells or tissue, Cohen-Karni et al 83 demonstrated for the first time recording from eletrogenic cells using single-layer graphene formed by mechanical exfoliation from graphite and carried out simultaneous recording using graphene and silicon nanowire FETs (Figure 7a …”
Section: Grapheneàdetection In Cellsmentioning
confidence: 99%